2013
DOI: 10.1093/icvts/ivt337
|View full text |Cite
|
Sign up to set email alerts
|

Does rich coronary collateral circulation distal to chronically occluded left anterior descending artery compete with graft flow?

Abstract: Rich collateral circulation distal to CTO in LADs can potentially compete with graft flow, although the competition seems not to affect clinical outcomes probably due to the regression of collaterals surmounted by the graft flow. Rentrop grade is shown to certainly reflect the degree of collateral haemodynamic circulation distal to CTO and especially important to evaluate intraoperative graft flow appropriately, considering the possible phenomenon of graft flow competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…We believe that the term competitive flow in this context is limited and does not adequately describe the “resistance to forward flow” downstream from a patent graft. As we summarized in Figure , other factors that might contribute to resistance and forward flow are as follows: the degree of proximal stenosis, flow from other grafts to the area, flow from coronary collaterals (particularly in the setting of chronically occluded arteries), size and quality of the grafted vessel, filling pressures of the heart chambers, and mean arterial perfusion pressure …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the term competitive flow in this context is limited and does not adequately describe the “resistance to forward flow” downstream from a patent graft. As we summarized in Figure , other factors that might contribute to resistance and forward flow are as follows: the degree of proximal stenosis, flow from other grafts to the area, flow from coronary collaterals (particularly in the setting of chronically occluded arteries), size and quality of the grafted vessel, filling pressures of the heart chambers, and mean arterial perfusion pressure …”
Section: Discussionmentioning
confidence: 99%
“…Graft failure is generally associated with the severity of the proximal stenosis, which in turn affects competitive flow from native vessels, other bypass grafts or collateral vessels, and the quality of the grafted vessel and tandem myocardium perfused by the grafted vessel . Differences between microvascular health and microvascular disease, as described by Gutterman et al may also play a fundamental role.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports regarding fate and effect of collateral circulation after CABG exist. Kaku and coresearchers have shown that the presence of rich collateral circulation can reduce graft flow and increase the pulsatility index and that preoperative collateral vessels can disappear after ITA grafting [12]. Takami and colleagues reported that the disappearance of collateral vessels may depend on the anastomosis location of ITA to LAD [13].…”
Section: Discussionmentioning
confidence: 99%
“…As explained in Section II, Kaku et al [17] found that retrograde collateral perfusion tends to be surmounted by ITA graft flow and disappears over time, since collateral channels are supposedly much smaller, providing greater resistance to flow than the ITA graft. Furthermore, ITA graft flow can increase over time, as collateral perfusion declines, since the ITA can autoregulate its flow depending on the demand and resistance of distal myocardial territories.…”
Section: -Studies That Conclude That Collateral Flow Does Not Inflmentioning
confidence: 97%
“…There are few papers reaching this conclusion; globally, these argue that the underlying mechanism is related to flow competition. Kaku et al [17] investigated whether a well-developed collateral circulation distal to chronically occluded left anterior descending artery competes with the flow of a distally anastomosed graft. Their patients were divided into three groups: Poor collaterals, Group P (Rentrop grade 0 or 1); Moderate collaterals, Group M (Rentrop grade 2); Rich collaterals, Group R (Rentrop grade 3).…”
Section: -Studies That Conclude That Good Collateral Flow Has a Dementioning
confidence: 99%